Síntese de 3-trifluoracetilpirróis N-substituídos - Wouters, Ana Dionéia (2008)
This work presents a new, simple and versatile one-pot strategy for the synthesis of new N-substituted 3-trifluoroacetyl-pyrroles. These compounds were obtained by the reaction of 3-trifluoroacetyl-4,5-dihydrofuran with primary amines (RNH2, where R = H, CH3, CH2CH3, CH(CH3)2, (CH2)2OH, CH2(C5H4N), CH2(C6H5), among others), generating 1,1,1-trifluoro-3-(2-hydroxyethyl)-4-alkylamino-3-buten-2-ones intermediates that in the most cases could not be isolated. Thus, in the same reaction pot they were directly submitted to oxidation reaction with PCC (Corey s Reaction) giving 1,1,1-trifluoro-3-(2-ethanal)-4- alkylamino-3-buten-2-ones, which under reflux underwent intramolecular cyclisation furnishing the desired N-substituted 3-trifluoroacetyl-pyrroles, in moderate yields (20-56%). The pyrroles obtained in this study were identified by NMR 1H, NMR 13C and Mass Espectroscopy.